Data and analysis scripts for: Statistical signature of electroburning in graphene nano-junctions - Evangeli, C; Tewari, S; Kruip, J; Bian, X; Swett, J; Cully, J; Thomas, J; Briggs, G; Mol, J (University of Oxford, 2022)
The electroburning trace data for all the substrates (SiO2, Al2O3, AlN, quartz) and scripts for creating the Figures in the manuscript are included in this submission.